Employing natural lighting systems technology in raising environmental efficiency in educational buildings - Saleem, Younis Mahmood; Abdul-Hameed, Saif Aldeen Saad Aldeen Saad (Iraqi Journal of Architecture and Planning, 2017)
Studies were carried out to increase dependence on day lighting to illuminate the buildings because of their psychological and health benefits ,and recent research has shown that exposure to artificial lighting for long periods cause health damage. As a result, many modern and sophisticated systems has emerged to introduce day lighting into the building to integrate with the traditional system (windows). These systems are based on advanced technology and can be available at relatively low cost, especially light tubes that integrated with traditional lighting (windows) to light deep spaces. Hence this research introduces new methodology added by using one of the modern lighting systems (light tubes) in the design process of buildings, and achieve coherence and efficiency in lighting levels inside the deep spaces by combining traditional and modern system, using computer. Hence the research problem consists in the lack of local studies that link traditional systems (Windows) and modern systems, particularly light tubes to light up the deep spaces. The goal of the research, is to integrate traditional systems (Windows) and modern systems, (light tubes), within a unified practical framework to employ light tubes locally in buildings. So this paper first dealt with day lighting technology systems and then chose the (light tubes) for its high efficiency, and distinctive characteristics apart from being inexpensive. Then the study adopted the rate of uniformity concluded from the application practical side to determine lighting levels and the efficiency of the merger between the two systems down to the final conclusions of the framework and the imposition of hypotheses.